OC-010 Final efficacy and safety in hcv genotype 1-infected patients receiving ombitasvir/paritaprevir/ritonavir and dasabuvir ± ribavirin: topaz-i results from the united kingdom and ireland. (17th June 2017) - Forton, D; Ustianowski, A; Aspinall, R; Ryder, S; Aldersley, M; Mutimer, D; Murray, F; McCormick, PA; Dillon, J; Foster, G; Agarwal, K; Charafeddine, M; et al.
Abstract : Introduction: Ombitasvir/paritaprevir*/ritonavir (*identified by AbbVie and Enanta) and dasabuvir (3-DAA) ± ribavirin (RBV) treatment is effective and safe for patients infected with hepatitis C genotype 1 (HCV GT1), including those with compensated cirrhosis. TOPAZ-I, an ongoing global phase 3b trial, assesses the impact of sustained virologic response (HCV RNA Method: The enrolled patients in TOPAZ-I received 3-DAA ± RBV, per label. These pooled, interim results included SVR12, adverse events (AEs), clinical outcomes, and liver stiffness evolution. SVR12 data were analysed using the intent-to-treat (ITT) population (missing data imputed as failures). Results: Among the 126 patients enrolled (table), the ITT SVR12 rate was 98%: one patient relapsed and 2 discontinued study drug prematurely, one due to AEs. AEs occurring in >10% of patients are listed in table. Six patients experienced serious AEs, none related to DAAs. Grade 3 laboratory abnormalities were rare and no Grade 4 abnormalities were reported. Three patients experienced adverse clinical outcomes, none deemed study drug-related: HCC (on treatment), fatal aspiration pneumonia (on treatment), and death from ischaemic heart disease (post-treatment week 18). Conclusion: These regional TOPAZ-I results confirm the efficacy and safety of 3-DAA ± RBV in HCV GT1-infected patients. Adverse clinical outcomes were rare. Liver stiffness changes post-treatment will be presented at the meeting. Disclosure of Interest: D. Forton Conflict with: participated in AbbVie-sponsored research, A. Ustianowski Conflict with: participated in AbbVie-sponsored research, R. Aspinall Conflict with: participated in AbbVie-sponsored research, S. Ryder Conflict with: participated in AbbVie-sponsored research, M. Aldersley Conflict with: participated in AbbVie-sponsored research, D. Mutimer Conflict with: participated in AbbVie-sponsored research, F. Murray Conflict with: participated in AbbVie-sponsored research, P. McCormick Conflict with: participated in AbbVie-sponsored research, J. Dillon Conflict with: participated in AbbVie-sponsored research, G. Foster Conflict with: participated in AbbVie-sponsored research, K. Agarwal Conflict with: participated in AbbVie-sponsored research, M. Charafeddine Conflict with: AbbVie employee and may own company stock, A. Joy Conflict with: AbbVie employee and may own company stock, L. Liu Conflict with: AbbVie employee and may own company stock, R.-M. Stanica Conflict with: AbbVie employee and may own company stock, T. Pilot-Matias Conflict with: AbbVie employee and may own company stock, M. O'Meara Conflict with: AbbVie employee and may own company stock, C. Pollard Conflict with: AbbVie employee and may own company stock, D. Cohen Conflict with: AbbVie employee and may own company stock, S. Norris Conflict with: participated in AbbVie-sponsored research